Problems of Environmental Conservation in the Himalayas - Joshi, H. B. (Indian Forester, 1986)
The Himalayan region has a unique importance for the rest of India, dominating as it does the climate the water Source etc. Environmental conservation of the Himalayan region when translated in actionable terms means to develop an integrated land use pattern according to natural suitability of the land, adoption of conservation promoting techniques in each land use, regulating activities like industrialization in consonance with environmental conservation and management of all natural resoures.